Dampak Screen Time Terhadap Kesehatan Mata, Pola Tidur Dan Konsentrasi Siswa - Eireine Maria Pandoh; Zefanya Pagayang; Aurelya Kairupan; Christy Legi; Imel Koraag; Jesika H.I Rondonuwu (STIKES Columbia Asia Medan, 2025)
The development of digital technology has significantly changed students’ lives, especially in learning and entertainment activities. However, the high intensity of using electronic devices such as smartphones, tablets, and computers has increased the amount of time spent in front of screens (screen time). Excessive screen time has adverse effects on eye health (e.g., dry and tired eyes), disrupts sleep patterns due to blue light exposure, and reduces students' concentration in learning. This community service program aimed to raise students' awareness and knowledge regarding the negative impact of prolonged screen time and provide education on mitigation strategies, such as the 20-20-20 rule, screen time limitations, and healthy sleep routines. The program was conducted through educational outreach and interactive discussions involving 88 students from grades X and XI at SMA Negeri 1 Tomohon in May 2025. Evaluation was carried out using pre-tests and post-tests along with feedback questionnaires. The results showed a significant improvement in students’ understanding of screen time risks and how to manage it. Participants also demonstrated high enthusiasm, as reflected in active involvement during Q&A sessions and their adoption of the tips provided. This program is expected to be the first step in fostering healthy digital habits among students.